Sinergi Hijau: Menggali Potensi Green Economy dalam Konteks Pariwisata Halal Indonesia - Makraja, Fahmi; Fitriyani, Elya; Afifah, Nisa (Jurnal Ilmiah Basis Ekonomi dan Bisnis, 2025)
Halal tourism in Indonesia has become one of the most promising sectors, but its development still faces challenges related to environmental sustainability. On the other hand, the Green Economy concept offers a solid framework for integrating economic, social, and environmental principles. This study aims to analyze the potential synergy between the Green Economy and halal tourism in Indonesia. Using a qualitative approach and literature review, this study explores how the implementation of green economy practices, such as the use of renewable energy, waste management, and conservation of natural resources, can enhance the competitiveness of halal tourism. The results indicate that the integration of these two concepts not only creates higher economic value but also strengthens the image of halal tourism as a responsible and sustainable sector. This synergy will drive product and service innovation, increase local community participation, and attract a growing market of environmentally conscious travelers. Therefore, this study recommends that the government and tourism industry stakeholders adopt policies and strategies that support the integration of halal and green principles to achieve a more sustainable tourism ecosystem in Indonesia.